Quality Assessment in the Service Area of Expertise in an Institution of Public Health Sector - Hernández Contreras, José Antonio; Esquivel Hernández, María Dolores; González Ponce, Ana María (Open Journal of Social Sciences, 2015)
In Mexico over time, economic crisis has worsened the health sector, where those most affected are the lower class, so that people with disease do not have access to private health services, given the high cost that this represents, just as people who are not beneficiaries of the Mexican Institute of Social Security by its Spanish initials IMSS, Institute of Security and Social Services for State Workers by its Spanish initials ISSSTE and other insured agencies providing public health services have no options to solve their health problems.
Keywords: Sector salud; Calidad del servicio; Servicio